Delayed diagnosis of spinal cord injuries in Huntington's disease. Issue 3 (4th February 2021) - Morrison, Hamish D; Morgan, Dafydd; McLauchlan, Duncan J; Clenaghan, Catherine; Rosser, Anne E
Abstract : Huntington's disease is a neurodegenerative disorder, characterised by progressive cognitive, motor and psychiatric symptoms. Patients with advanced disease presenting to emergency medical services can pose a diagnostic and management challenge for physicians unfamiliar with the condition. We describe two patients with Huntington's disease in whom the diagnosis of traumatic spinal cord injury was delayed, discuss the role that cognitive bias and other factors played in this delay, and the lessons we can learn.